2016
DOI: 10.1108/raf-06-2014-0059
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy prediction: the case of Belgian SMEs

Abstract: Purpose-The aim of this paper is to develop a bankruptcy prediction model for the Belgian smalland medium-sized enterprises (SMEs) through the building of a logit model that includes a selection of financial ratios. Design/methodology/approach-Using a sample of 7,152 Belgian SMEs among which 3,576 were declared bankrupt between 2002 and 2012, the model, which includes control variables such as firm size and age, aims to test the predictive power of ratios reflecting the financial structure, the profitability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 36 publications
4
60
0
2
Order By: Relevance
“…[28] using NN, the Cox model and Logit managed to correctly predict 81.20% of bankruptcy cases, using a sample of French firms for their models. [12] developed a Logit bankruptcy prediction model based on Belgian firms, including control variables such as the size and age. The results showed that ratios of profitability and liquidity increase the accuracy of bankruptcy prediction.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] using NN, the Cox model and Logit managed to correctly predict 81.20% of bankruptcy cases, using a sample of French firms for their models. [12] developed a Logit bankruptcy prediction model based on Belgian firms, including control variables such as the size and age. The results showed that ratios of profitability and liquidity increase the accuracy of bankruptcy prediction.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…This has also resulted in a new area of research, given the need to create models to predict bankruptcy, not just for a given country, but also to explain the common features shared by companies in the same geographical setting [8]. However, when creating models that attempt to offer rigorous predictions of bankruptcy, the majority of these have centred on companies in a single country or industry [912] or have focused on comparing the results of different predictive models, but without considering the creation of a global model [8]. …”
Section: Introductionmentioning
confidence: 99%
“…The abundance of scientific literature reveals the necessity for a reliable, precise and relevant bankruptcy prediction model. According to Aruldoss et al (2015), Cultrera and Bredart (2016), Salehi and Pour (2016), the information rendered by bankruptcy forecasting models is bounded to separate industries. Alaka et al (2018), Schonfeld et al (2018), Svabova and Kliestik (2018), and Slefendorfas (2016) believe that the traditional bankruptcy prediction models are not suited to analyzing modern enterprises because the dynamic macroeconomic environment and business are interdependent.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Han [25] used non-financial information, such as type of business, number of employees, number of exports, and technical manpower ratings, to build a prediction model along with financial information. In addition to the financial ratio, the types of non-financial information used for insolvent prediction were based on research focusing on industry sector, region, and company age [26,27]; the quality of accounting information, firm owners' personal credit performance, and management quality [28]; context-based feature set designing industry-representative models [19]; and indicators such as value-added rate and labor productivity [29]. The prediction rates for these studies ranged from 74.1% to 93%.…”
Section: Research On Predicting Company Insolvencymentioning
confidence: 99%